(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2023)
The craft of Durrie weaving has undergone many changes over the last few decades. This traditional craft, which was a common household practice initially, is still practiced in some districts of Punjab. The craft is learned mainly from the elders of the family as there are no formal training centres to impart the skill and preserve the art form. Majority of the respondents are involved with the craft along with the senior members of the family. Durrie, rugs and foot mats are the most common articles prepared by the artisans. High cost of production and low wages for the artisans as well as lack of a good marketing network are the major challenges faced by the respondents. Absence of attractive promotion opportunities on a regular platform is hampering the demand for these traditional products which are a part of our heritage and need to be preserved for our future generations.